SURVIVAL STRATEGIES OF TRADITIONAL MARKET TRADERS IN THE DIGITAL ERA: A CASE STUDY ON THE TRANSFORMATION TO MODERN MARKET - Br Purba, Devia Syahfitri; Yazid Tanjung, Hafiz; Saragih, Murniati Arinda; Permatasari, Putri Dwi (Academic Solution Publisher, 2024)
This study seeks to examine the survival strategies adopted by traditional market traders in the digital age, concentrating on the evolution of the Usus Tax Market into a contemporary marketplace. In recent years, the advancement of digital technology has influenced nearly all areas of life, including the trade sector. Traditional markets, which originally relied on direct face-to-face interactions between traders and consumers, are currently encountering new challenges stemming from advancements in information technology and e-commerce platforms. This research employs a qualitative methodology, utilizing a case study approach to examine the Gut Tax Market, which has undergone a transformation into a contemporary market from both physical and digital viewpoints. The research findings indicate that traders at the Usus Tax Market have implemented a range of strategies, including the utilization of social media, online shopping applications, and the advancement of digital payment systems to enhance their competitiveness. In addition, alterations in consumption patterns and market preferences are significant factors that impact traders' survival strategies. This research offers valuable insights into the ways traditional markets can endure and evolve in response to technological advancements while maintaining their unique attributes and sustainable viability.